PEMAKAIAN AKSARA DALAM PENULISAN BAHASA MELAYU HINGGA BAHASA INDONESIA (THE USAGE OF LETTERS ON MALAY TO INDONESIAN LANGUAGE WRITING) - Akhmad Yazidi (JURNAL BAHASA, SASTRA DAN PEMBELAJARANNYA, 2013)
AbstractThe Usage of Letters on Malay to Indonesian Language Writing. This paper discussesthe history of the Indonesian language, literacy in the writing of a variety of languages, Malay letter in writing to the Indonesian language, and spelling in Indonesian. Ofthis section may conclude that in writing the history of written language or alphabetletters contained Paku, the letter Babylonian, Assyrian letters, letters of Ancient Persia;Pallawa, Kawi Letter used in Sanskrit; Arabic, Kanjiin Japanese and Chinese, letters,Jawi Premodern, Modern Java, Bali Modern: literacy Hanacaraka from Lampung,Rencong, Karo Batak, Bugis-Makassar as well;and Latin script. Indonesian languagethat comes from the Malay language has a long history, There are some developmentspase formation of the Indonesian language, namely Old Malay, Malay Market, HigherMalay, and Bahasa Indonesian. Since the 5th century inscription has been found to beYupa in Kutai in East Kalimantan with a script and inscription Pallawa Tarumanegara,and inscriptions in Old Malay inscriptions in a script that is Pallawa Towu Gutters,Cape Inscription Land, and the inscription Limestone City. In a later development afterthe Arabs came to trade missions and preaching, use Malay Arabic script known asJawi letters, and beginning of the 20th century the concept put forward by the Ch. A.Dutch van Ophuysen applied linguists Latin letters into the Malay language. Ever seenon the spelling of force, then in the Indonesian language contained van OphuysenSpelling, Spelling Republic, and Spelling Enhanced.Keywords: letter of the alphabet, spelling, languageAbstrakPemakaian Aksara dalam Penulisan Bahasa Melayu hingga Bahasa Indonesia. Tulisanini membahas tentang sejarah bahasa Indonesia, aksara dalam penulisan berbagaibahasa, aksara dalam penulisan bahasa Melayu hingga bahasa Indonesia, dan ejaandalam bahasa Indonesia. Dari pembahasan ini dapat disimpulkan bahwa dalam sejarahtulisan atau aksara bahasa tulis terdapat huruf Paku, yaitu huruf Babylonia, hurufAssyiria, Huruf Persia Kuno; Pallawa, Huruf Kawi yang digunakan dalam bahasaSanskerta; huruf Arab, huruf Kanji dalam bahasa Jepang dan Cina, huruf, JawiPramodern, Jawa Modern, Bali Modern; Aksara Hanacaraka dari Lampung, Rencong,Batak Karo, serta Bugis-Makassar; serta aksara Latin. Bahasa Indonesia yang berasaldari bahasa Melayu mempunyai sejarah yang cukup lama, Terdapat beberapa faseperkembangan terbentuknya bahasa Indonesia, yaitu bahasa Melayu Kuno, MelayuPasar, Melayu Tinggi, dan Bahasa Indonesia. Sejak abad ke-5 sudah ditemukan prasastiberupa Yupa di Kutai Kalimantan Timur dengan aksara Pallawa dan PrasastiTarumanegara, kemudian prasasti dalam bahasa Melayu Kuno dalam aksara Pallawa,yaitu Prasasti Talang Towu, Prasasti Tanjung Tanah, dan Prasasti Kota Kapur. Dalamperkembangan kemudian setelah bangsa Arab datang dengan misi dagang dan dakwah,48digunakan aksara Arab Melayu yang dikenal sebagai huruf Jawi, dan awal abad ke-20atas konsep yang di kemukakan oleh Ch. A. van Ophuysen ahli bahasa Belandaditerapkan huruf Latin kedalam bahasa Melayu. Dilihat dari ejaan yang pernah berlaku,dalam bahasa Indonesia terdapat Ejaan van Ophuysen, Ejaan Republik atau EjaanSuwandi, dan Ejaan Yang Disempurnakan.Kata-kata kunci: aksara, ejaan, bahasa